ExPeKT—Exploring prevention and knowledge of venous thromboembolism: a two-stage, mixed-method study protocol. Issue 4 (2nd April 2013) - McFarland, Lorraine; Ward, Alison; Greenfield, Sheila; Murray, Ellen; Heneghan, Carl; Harrison, Sian; Fitzmaurice, David
Abstract : Introduction: There is little awareness of venous thromboembolism (VTE) in the public arena. Most commonly known causes are—travellers' thrombosis and thrombosis associated with oral contraception, both frequently referred to in the media. However, VTE is a substantial healthcare problem, resulting in mortality, morbidity and economic cost. Most hospitalised patients have one or more risk factors for VTE. Around 60% of people undergoing hip or knee replacement will suffer a deep vein thrombosis without preventative intervention. Studies demonstrate a risk reduction for VTE of up to 70% with preventative medicine for medical and surgical conditions: cancer, orthopaedic surgery, general surgery and acutely ill medical admissions. Results will be used to identify methods of increasing knowledge of VTE prevention and for the development of educational and patient information materials. Methods and analysis: A two-stage, mixed-method study using surveys with primary healthcare professionals and patients followed by interviews with primary healthcare professionals, patients, acute trusts and other relevant organisations. Survey and qualitative interview data will examine the current practice of thromboprophylaxis, and the knowledge and experience of VTE prevention for the development of education initiatives for primary healthcare professionals and patients to adopt thromboprophylaxis outside the hospital setting. As this is a scientific exploratory study for the generation, rather than testing, of new hypotheses a sample-size analysis is not called for. Survey data will be analysed using SPSS version 20. Open-ended responses will be analysed using qualitative thematic methods. The recorded and transcribed semistructured interview data will be analysed using constant comparative methods. Ethics and dissemination: Ethics approval has been provided by the National Research Ethics Committee (reference: 11/H0605/5) and site-specific R&D approval granted by the relevant R&D National Health Service trusts. Findings will be disseminated at healthcare and academic conferences and written for peer-reviewed publication. Trial grant number: NIHR RP-PG-0608-10073